The pattern of refractive error associated with the different ABO blood group among the drivers attending the driving school of Al Ahsa region of Saudi Arabia - Ali, Ayub; Qureshi, Habib Ahmad (Edelweiss Applied Science and Technology, 2025)
ABO blood grouping system is pivotal in blood transfusion. Blood group selection can be influenced by environmental, geographical conditions and migration frequency of the population. Association between ABO and refractive error has been established by many studies. The present study was conducted in Al Ahsa region of Saudi Arabia to determine the frequency of ABO and Rh blood groups among the people seeking for driving licenses of different nationality and ethnic group and its association with the refractive error. It was a cross sectional survey conducted on the subjects attending for medical examination for their driving license renewal /new license. All the subjects seeking driving license at the main medical exam center of driving school of Al Ahsa during the study period was the study population. The sample size was calculated using a Fisher‟s formula cited by Mugenda & Mugenda (1999) which was calculated as 1689 in number The sampling was done by convenience sampling method till the sample size is achieved. A data collection sheet was prepared to record the age, sex, nationality and blood group and status of refraction of the eyes. The collected data were cleared, coded, entered and analyzed by the SPSS version 26. A p-value cut off point of 0.05 at 95% CI was used to determine statistical significance. A total of 1593 subjects were examined during the study period. The mean age of the participants was 30.98 ± Std. Dev. 10.21. The vast majority of the participants were Male (94.6%). A total of around 15% of the participants with blood group O+ were suffering from refractive error of which 7.5% each were suffering from Myopia and Hypermetropia. Myopia was significantly more among participants with O+ blood gro (P=0.000). Hypermetropia was significantly more common among the participants with blood group AB- (p =0.000). The present study has shown that Myopia was significantly more among participants with O+ blood group than other blood group. Hypermetropia was significantly more common among the participants with blood group AB- as compared to other blood groups. However, there is a need of larger cohort study to confirm any association of ABO blood group with refractive error.